2010
DOI: 10.1088/0953-4075/43/24/245503
|View full text |Cite
|
Sign up to set email alerts
|

Sign reversal of Hanle electromagnetically induced absorption with orthogonal circularly polarized optical fields

Abstract: We study by computation and experiment an electromagnetically induced absorption resonance in the Hanle configuration with a transverse magnetic field on a closed Fg → Fe = Fg+1 transition with co-propagating orthogonal circularly polarized probe and coupling optical fields. At high coupling field intensities, the Hanle resonance changes sign due to a shift in atomic population from Zeeman sublevels associated with a probe field cyclic transition to sublevels associated with a coupling field cyclic transition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 13 publications
1
6
0
Order By: Relevance
“…The effect is opposite in the co-propagating configuration. Reversal of the coherent resonances has been previously reported with co-propagating beams and only partial accumulation of atoms in the bright state [16]. In our work, by taking advantage of the overlapping of the K ground state hyperfine components and of the optical transitions of its D 1 line, we obtain the same efficiency of accumulation in states forming bright or dark resonances, depending on the experimental conditions, which can be easily tuned, as demonstrated in the following.…”
supporting
confidence: 70%
See 1 more Smart Citation
“…The effect is opposite in the co-propagating configuration. Reversal of the coherent resonances has been previously reported with co-propagating beams and only partial accumulation of atoms in the bright state [16]. In our work, by taking advantage of the overlapping of the K ground state hyperfine components and of the optical transitions of its D 1 line, we obtain the same efficiency of accumulation in states forming bright or dark resonances, depending on the experimental conditions, which can be easily tuned, as demonstrated in the following.…”
supporting
confidence: 70%
“…Low-contrast EIA, resulting from EIT on D 2 line, was reported. Higher contrast EIA has been observed in [16], although overlapped to large background, which could be detrimental for highly-selective applications. More recently, sub-kHz EIA resonances were observed in Rb [17] and Cs [18,19].…”
mentioning
confidence: 99%
“…In this case, one often refers to the phenomenon as a nonlinear magneto-optical resonance, which can be bright or dark, as the absorption at zero magnetic field represents a local maximum or minimum, respectively. Recently, attention has been focused on the conversion of EIT to EIA as a function of the properties of the pump field, such as polarization [4] and laser power density [5][6][7][8]. In this work we describe the conversion of a bright nonlinear magnetooptical resonance to a dark resonance as a function of the laser power density of the single optical field and the temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Working with two coherent laser fields, Kim et al observed the conversion of EIT to EIA as a function of the coupling laser power in the D 1 line of rubidium [5]. Other groups have also studied the influence of coupling laser power on EIT and EIA in different systems and for different polarizations of the coherent fields [6][7][8]22]. Brazhnikov et al have studied the effect of the polarization of counterpropagating fields on EIT and EIA [4].…”
Section: Introductionmentioning
confidence: 99%
“…1. MIT and MIA have been studied before, but only separately [8][9][10][11] 2. Only the transformation from MIA to MIT (using transitions in the D 1 line of Rb) has been studied before [12,13].…”
Section: Introductionmentioning
confidence: 99%